Bacterially Synthesized Tellurium Nanorods for Elimination of Advanced Malignant Tumor by Photothermal Immunotherapy. Issue 8 (9th December 2021) - Yao, Yuzhu; Li, Jianye; Li, Puze; Wang, Dongdong; Bao, Wei; Xiao, Yi; Chen, Xue; He, Shuaicheng; Hu, Jun; Yang, Xiangliang
Abstract: Probiotic Escherichia coli Nissle 1917 (EcN) are employed as a bioreactor for intracellularly synthesizing tellurium nanorods (TeNRs) providing a biohybrid therapeutic platform (Te@EcN) for the elimination of advanced malignant tumor by photothermal immunotherapy. Te@EcN is found to possess superior photothermal property upon near‐infrared irradiation, and can efficiently accumulate and retain in tumors, although EcN loses proliferation ability after the synthesis of TeNRs, thus inducing considerable immunogenic tumor cell death. Under co‐stimulation by EcN acting as immunoadjuvants, maturation of dendritic cells and priming of cytotoxic T cells are largely promoted. In addition, Te@EcN can reprogram tumor‐associated macrophages to ameliorate the immunosuppressive tumor microenvironment. Thus, tumor metastasis and recurrence can be efficiently suppressed. Most importantly, owing to the non‐pathogenicity of probiotic EcN and their non‐proliferative characteristics after TeNRs synthesis, Te@EcN is found to be rapidly metabolized and cleared from the normal tissues, showing very slight acute side effects in healthy mice even at a relatively high administration dose. Therefore, the proposed combined therapeutic strategy based on bacteria‐synthesized TeNRs may find great potential in improving bacteria‐mediated tumor therapy with increased antitumor efficacy and reduced toxicity. Abstract : A biohybrid therapeutic platform by biosynthesizing tellurium nanorods inside Escherichia coli Nissle 1917 (EcN) is developed for antitumor photothermal immunotherapy. The obtained Te@EcN demonstrates prominent tumor targeting and retention effects, photothermal performances, and immunomodulatory properties, with Te as the near‐infrared photothermal agent and EcN as the carrier and immune adjuvant, leading to potent antitumor effects and improved biosafety.